2017
DOI: 10.1111/mms.12424
|View full text |Cite
|
Sign up to set email alerts
|

Fecal cortisol radioimmunoassay to monitor adrenal gland activity in the bottlenose dolphin (Tursiops truncatus) under human care

Abstract: Fecal glucocorticoid measurement is an important noninvasive tool to monitor animal health. A radioimmunoassay (RIA) method was developed to measure fecal cortisol in bottlenose dolphins under human care. The method was used to measure baseline hormone levels and evaluate the adrenal response to environmental challenges in a small number of individual dolphins. The method was validated by precision and accuracy tests and by comparison with liquid chromatography‐mass spectrometry (LC‐MS). The parallelism test s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…Further, Champagne et al (2018) observed an increase in fecal cortisol metabolites at 4.5 h after initiation of the stressors. Biancani et al (2017) did not detect a rise in FGCMs after a prolonged transport stressor, with sampling at 1, 24, and 27 h post-transport, supporting the premise that the rise in FGCMs in their study was missed because it occurs within a 1-24 h period post-stressor, and possibly between 4 and 8 h post-stressor. An increased sampling frequency and successful fecal collection may have increased our chances of detecting a change, if indeed one was present to detect.…”
Section: Biological Stress Responsementioning
confidence: 50%
See 2 more Smart Citations
“…Further, Champagne et al (2018) observed an increase in fecal cortisol metabolites at 4.5 h after initiation of the stressors. Biancani et al (2017) did not detect a rise in FGCMs after a prolonged transport stressor, with sampling at 1, 24, and 27 h post-transport, supporting the premise that the rise in FGCMs in their study was missed because it occurs within a 1-24 h period post-stressor, and possibly between 4 and 8 h post-stressor. An increased sampling frequency and successful fecal collection may have increased our chances of detecting a change, if indeed one was present to detect.…”
Section: Biological Stress Responsementioning
confidence: 50%
“…Liquid chromatographymass spectrometry (LCMS) analysis of bottlenose dolphin feces revealed that native cortisol but not corticosterone was present, suggesting that antibodies that react with cortisol are sufficient for quantifying cortisol in bottlenose dolphin feces (Biancani et al, 2017). However, Biancani et al (2017) did not fully examine Abs eos #F 1,68 = 8.2, P = 0.006 mR 2 = 0.10, mP = 0.003…”
Section: Cross-reactivity and Correlation Of Steroid Metabolites In Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the total amount of droppings' corticosterone metabolites were positively correlated with plasma corticosterone, indicating that droppings' corticosterone metabolites could also be used to diagnose stress response (Bradely and Holmes 1971;Culbert and Wells 1975;Teskey-Gerstl et al 2000b;Dehnhard et al 2001). And it has been already used to investigate questions in the fields of "stress and animal welfare, reproductive, physiology, and behavioral ecology" (Turriani et al 2016;Yarnell et al 2016;Biancani et al 2017;Cao et al 2017;Webster et al 2017;Cinque et al 2018;Wolf et al 2018), such as fighting against spotted hyenas (Goymann et al 1999), drought or social stress on African elephants (Foley et al 2001), catching stress on laying hens (Fraisse and Cockrem 2006), mercury exposure to tern stress (Herring et al 2012), and heat stress on broilers ( Su et al 2014a/b? ).…”
Section: Introductionmentioning
confidence: 99%
“…Radioimmunoassay (RIA) is the most common analytical method used to measure steroids with good sensitivity and reproducibility 18,19 . RIA is gradually being replaced by enzyme-linked immunosorbent assays (ELISA) because of legislation relating to laboratory waste 20,21 .…”
mentioning
confidence: 99%